2019
DOI: 10.1016/j.cmet.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Non-Canonical Control of Neuronal Energy Status by the Na+ Pump

Abstract: Highlights d Neuronal ADP:ATP is not affected by neurotransmission despite strong Na + pumping d Stimulated mitochondrial pyruvate flux precedes glucose consumption d Energy stability is not explained by conventional homeostasis (ADP:ATP or Ca 2+) d Na + pump activity controls glycolysis and mitochondrial ATP production

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
95
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 78 publications
13
95
1
Order By: Relevance
“…In contrast to activity and stimulation patterns that involved global [Na + ] i elevations, spatially restricted local [Na + ] i influx as observed upon brief pressure application of glutamate onto dendrites did not evoke a detectable decrease in [ATP] i . A recent study that failed to observe changes in somatic ATP levels in response to electrical activity and Na + influx concluded that ATP consumption by the NKA is matched by a direct increase in mitochondrial ATP production (Baeza-Lehnert et al 2019). Earlier work by us and other laboratories, together with the results presented here, provides an alternative and/or additional explanation for the lack of changes in neuronal [ATP] levels despite relevant increases in [Na + ] i and the efficient recovery thereof.…”
Section: Relation Between Sodium and Atpmentioning
confidence: 49%
See 3 more Smart Citations
“…In contrast to activity and stimulation patterns that involved global [Na + ] i elevations, spatially restricted local [Na + ] i influx as observed upon brief pressure application of glutamate onto dendrites did not evoke a detectable decrease in [ATP] i . A recent study that failed to observe changes in somatic ATP levels in response to electrical activity and Na + influx concluded that ATP consumption by the NKA is matched by a direct increase in mitochondrial ATP production (Baeza-Lehnert et al 2019). Earlier work by us and other laboratories, together with the results presented here, provides an alternative and/or additional explanation for the lack of changes in neuronal [ATP] levels despite relevant increases in [Na + ] i and the efficient recovery thereof.…”
Section: Relation Between Sodium and Atpmentioning
confidence: 49%
“…A recent study that failed to observe changes in somatic ATP levels in response to electrical activity and Na + influx concluded that ATP consumption by the NKA is matched by a direct increase in mitochondrial ATP production (Baeza‐Lehnert et al . ). Earlier work by us and other laboratories, together with the results presented here, provides an alternative and/or additional explanation for the lack of changes in neuronal [ATP] levels despite relevant increases in [Na + ] i and the efficient recovery thereof.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…From previous studies in mammalian cells, it has been proposed that glial‐derived lactate can supply the energy requirements for neuronal function. However, it is still a matter of debate whether this mechanism operates in vivo during resting states or during increased neuronal activity (Baeza‐Lehnert et al, ; Barros & Weber, ; Diaz‐Garcia & Yellen, ; Dienel, ). In Drosophila , glial glycolysis is necessary for survival, suggesting that transport of lactate from glial cells fuels neurons (Volkenhoff et al, ).…”
Section: Resultsmentioning
confidence: 99%